Berbagai Faktor Risiko Kejadian Bayi Berat Lahir Rendah (BBLR) (Studi di Beberapa Puskesmas Kota Makassar) - Hasriyani Hasriyani; Suharyo Hadisaputro; Kamilah Budhi; Mexitalia Setiawati; Henry Setyawan (Master of Epidemiology, School of Postgraduate Studies, Diponegoro University, Indonesia, 2018)
Background: Low-birth-weight (LBW) as community health problem have remained as the main cause of prenatal morbidity and mortality. In Indonesia, the occurrence rate of LBW has reached 10,2%. LBW has caused by multifactors such as maternal factor, fetus factor, and environmental factor. The aim of the study was to elaborate if maternal factor and environmental factor are the risk factors contributing to LBW occurrence.Method: The study was based on case control design. The number of samples was 138 respondents who were categorized into 69 cases and 69 controls fulﬁlling the criteria of inclusion and exclusion. The cases were mothers with babies having birth weight <2500 grams regarding the gestational age, and the controls were mothers with babies having birth weight ≥2500 grams regarding the gestational age. Sampling method to the cases was conducted by consecutive sampling while sampling to the controls was conducted by simple random sampling with matching to sex and location.Results: Maternal factors observed as risk factors contributing to LBW are low nutritional status (OR=5.357; 95%CI=1.985-14.457), illness pregnancy (OR=3.976; 95%CI=1.669-9.476). Maternal factors and environmental factors observed as non-risk factors to LBWN are age < 20 years old or age > 35 years, the spacing of pregnancy < 2 years, the of family members smoking at home, the of a food taboos culture, ANC status < 4x , low social economy status.Conclusion: Low nutritional status, illness pregnancy are risk factors contributing to LBW occurrence. The probability of LBW occurrence when those risk factors observed are 68,87%.